2009
DOI: 10.1016/j.taap.2009.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of endothelial monocyte chemoattractant protein-1 by coplanar PCB77 is caveolin-1-dependent

Abstract: Atherosclerosis, the primary cause of heart disease and stroke is initiated in the vascular endothelium, and risk factors for its development include environmental exposure to persistent organic pollutants. Caveolae are membrane microdomains involved in regulation of many signaling pathways, and in particular in endothelial cells. We tested the hypothesis that intact caveolae are required for coplanar PCB77-induced up-regulation of monocyte chemoattractant protein-1 (MCP-1), an endotheliumderived chemokine tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 42 publications
2
73
0
1
Order By: Relevance
“…1b). Up-regulation of endothelial MCP-1 by PCB77 has been recently verified by Majkova et al (2009), who considered that the increase of MCP-1 by PCB77 is caveolin-1-dependent. But the adhesion assay has not yet been detected.…”
Section: Inflammatory Response Induced By Pcb77mentioning
confidence: 81%
“…1b). Up-regulation of endothelial MCP-1 by PCB77 has been recently verified by Majkova et al (2009), who considered that the increase of MCP-1 by PCB77 is caveolin-1-dependent. But the adhesion assay has not yet been detected.…”
Section: Inflammatory Response Induced By Pcb77mentioning
confidence: 81%
“…Our data suggest a similar synergistic effect on CCL-2 secretion in APM-treated endothelial cells. This could have important implications for systemic disease associated with APM exposure as CCL-2 plays a key role in the vascular and renal consequences of the metabolic syndrome (15,36,54). Finally, CEBPD has been reported to enhance CCL-2 transcription separate from NF-B activity in vascular smooth muscle cells (60).…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, when in the presence of PCB 77, CYP1A1 can become uncoupled and increase the levels of cellular reactive oxygen species (ROS), leading to induction of pro-inflammatory genes and subsequent vascular dysfunction (Kopf & Walker, 2010). Our laboratory has demonstrated previously that exposure to PCB 77 increases the expression of vascular cell adhesion molecule-1 (VCAM-1) (S G Han, Eum, Toborek, Smart, & Hennig, 2010), endothelial-derived monocyte chemoattractant protein-1 (MCP-1) (Majkova, Smart, Toborek, & Hennig, 2009), and interleukin-6 (IL-6) (Hennig et al, 2002). Other groups have shown that PCBs impair endothelium-dependent dilation (Helyar et al, 2009) and promote obesity-associated atherosclerosis (Arsenescu, Arsenescu, King, Swanson, & Cassis, 2008).…”
Section: Introductionmentioning
confidence: 99%